A meta-analysis of the association of aircraft noise at school on children's reading comprehension and psychological health for use in health impact assessment. (August 2021) - Clark, Charlotte; Head, Jenny; Haines, Mary; van Kamp, Irene; van Kempen, Elise; Stansfeld, Stephen A.
Abstract: Whilst the effects of aircraft noise on children's cognition are well-accepted, their application in Health Impact Assessment (HIA) and methodologies to monetise the effects of noise on health have been limited. This paper presents the first meta-analysis of the effect of aircraft noise at school on children's reading comprehension and psychological health assessed with the Strengths and Difficulties Questionnaire. Data from three methodologically similar studies carried out in 106 schools near London Heathrow, Amsterdam Schiphol, and Madrid Barajas airports (the Schools Environment and Health Study, the West London Schools Study, and the RANCH study) were analysed finding that a 1 dB increase in aircraft noise exposure at school was associated with a −0.007 (95%CI −0.012 to −0.001) decrease in reading score and a 4% increase in odds of scoring well below or below average on the reading test. The analyses also found that a 1 dB increase in aircraft noise exposure at school was associated with a 0.017 (95%CI 0.007–0.028) increase in hyperactivity score. No effects were observed for emotional symptoms, conduct problems or Total Difficulties Score. Meta-analyses confirm existing evidence for effects of aircraft noise exposure on children's reading comprehension, providing a pooled estimate and exposure-effect relationship, as well as additional estimates and relationships for effects on scoring 'well below or below average' on the reading test offering flexibility for taking reading comprehension into account in HIA and monetisation methodologies in a wide-range of contexts. Highlights: First meta-analysis estimate of aircraft noise on children's reading comprehension. Additional new estimates for scoring 'well below or below average' on the reading test. Meta-analysis confirms effects of aircraft noise on hyperactivity but no effect on conduct problems or emotional symptoms. Innovative analyses offering flexibility for use in Health Impact Assessment. Informs communities impacted by airport development.